As media image builders of man and woman in Ciudad Juárez (México) and Armenia (Colombia) - Larrarte, Sandra Leal; Pérez García, Martha Estela (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
One of the futures of the media is reflecting surface communication system (Serrano, 2004), based on themes already naturalized as gender, thought this as part of the cultural construction means, controls ad action difference both men and women. Through the language used by the media expressed patriarchal system concepts. Appliying the proposed Van Dijk (2001) and Molero (2005), one can recognize how the media of cities like Armenia in Colombia and Ciudad Juarez in Mexico, entered this mind with regard to gender.